2022
DOI: 10.1093/ej/ueac083
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Cuts and Crime: Evidence from the New Poor Law

Abstract: The New Poor Law reform of 1834 induced dramatic and heterogeneous reductions in welfare spending across English and Welsh counties. Using the reform in a difference-in-differences instrumental variables strategy, we document a robust negative relationship between the generosity of welfare provision and criminal activity. Results are driven by non-violent property crimes and are stronger during months of seasonal agricultural unemployment, highlighting the particularly criminogenic combination of welfare cuts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(81 reference statements)
0
0
0
Order By: Relevance
“…The results revealed that social welfare expenditures reduced crime rates and had the most significant inhibitory effect on property crime. The above findings have also been confirmed in many subsequent studies [44,45].…”
Section: R E T R a C T E Dsupporting
confidence: 79%
See 1 more Smart Citation
“…The results revealed that social welfare expenditures reduced crime rates and had the most significant inhibitory effect on property crime. The above findings have also been confirmed in many subsequent studies [44,45].…”
Section: R E T R a C T E Dsupporting
confidence: 79%
“…Existing studies show that increases in the unemployment rate, which damages the welfare of local residents and intensifies social tensions, will raise the theft crime rate. A high incidence of theft activities, in turn, makes low-skilled workers more susceptible to exclusion and reduces the opportunity cost of theft, which further leads to an increase in theft crime [45]. On the contrary, a rise in the income from legal work leads to an increase in the opportunity cost of theft.…”
Section: Hypothesis 1 (H1) the Development Of Digital Financial Inclu...mentioning
confidence: 99%